Hi, I have a question regarding simplifying the following expression:

(1/x)/((1/3)x^(-2/3)) = 3/3sqrtx

The last expression reads three over cube root of x. I don't understand how to get from the expression on the left side of the equal sign to the one on the right.

Could somebody please help me out?

Your help would be greatly appreciated!

3 answers

multiplying by 1/3
... (1/x) / [x^(-2/3)] = 1 / [x^(1/3)]

multiplying by x^(-2/3)
... 1/x = [x^(-2/3)] / [x^(1/3)]
... = 1 / [x^(3/3)] = 1/x
re-writing your equation:

(1/x)/((1/3)x^(-2/3)) = 3/x^(1/3)

(3/x) x^(2/3) = 3/ x^(1/3)
divide by 3
(1/x) x^(2/3) = 1/x^(1/3)
multiply both sides by x^(1/3)
(1/x)(x)^1 = 1
1 = 1

so the equation is true for all x, except of course x = 0, or else we would be dividing by zero
Thank you for your help, Scott and Reiny.
Similar Questions
  1. Consider these expressionsExpression 1: 3.4(2m - 4) Expression 2: 4(5.1 - 2.3m) Expression 3: 2.2(0.16m + 3) Emma applies the
    1. answers icon 1 answer
  2. application of the laws of exponent.show different ways of simplifying each of the following expression. answer the question
    1. answers icon 2 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions